2018
DOI: 10.4054/demres.2018.39.16
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in personal fertility ideals among U.S. women in heterosexual relationships

Abstract: BACKGROUND Demographers typically ask about societal, not personal, fertility ideals. Societal ideals are probably more stable than personal ideals. Assessing whether personal fertility ideals are as stable as societal ideals could inform models of population fertility change and models of well-being associated with fertility outcomes. METHODS We use the two-wave National Survey of Fertility Barriers (NSFB) to model stability and change in fertility ideals among 879 women in heterosexual couples that persisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…In the USA, increases in expectations over time were associated with initially desiring fewer than two children (Quesnel-Vallee & Morgan, 2003) and with sequential childbearing. The size of the effect, however, appears larger for higher parities (Heiland et al, 2008;Miller & Pasta, 1995;Ray et al, 2018) and for those who have positive previous birth experiences (Iacovou & Tavares, 2011).…”
Section: Background Expectations Over the Life Coursementioning
confidence: 86%
See 3 more Smart Citations
“…In the USA, increases in expectations over time were associated with initially desiring fewer than two children (Quesnel-Vallee & Morgan, 2003) and with sequential childbearing. The size of the effect, however, appears larger for higher parities (Heiland et al, 2008;Miller & Pasta, 1995;Ray et al, 2018) and for those who have positive previous birth experiences (Iacovou & Tavares, 2011).…”
Section: Background Expectations Over the Life Coursementioning
confidence: 86%
“…Although some have used cross-sectional samples to infer change (Testa & Grilli, 2006), the more convincing explorations come from studies that follow individuals longitudinally. Putting to one side a growing literature on expectations over time among childless individuals, studies looking at expectations among women with children find that there is a considerable number who do have stable expectations, particularly among those desiring two children (Heiland, Prskawetz, & Sanderson, 2008;Quesnel-Vallee & Morgan, 2003) and in USA analyses (Quesnel-Vallee & Morgan, 2003;Ray, Harcey, Greil, Tiemeyer, & McQuillan, 2018). The studies also highlight, however, sizeable adjustments of intentions over the life course among other groups.…”
Section: Background Expectations Over the Life Coursementioning
confidence: 99%
See 2 more Smart Citations
“…This no tion is supported in other re cent stud ies in de vel oped con texts. For ex am ple, Ray et al's (2018) study of the sta bil ity of per sonal fer til ity ide als among U.S. women us ing two waves of data from the National Survey of Fertility Barriers found that one-third of women ad justed their ideal num ber of chil dren in ei ther di rec tion be tween waves. Such findings on both the sta bil ity of fer til ity de sires and con ver gence be tween intended and achieved par ity are also con di tioned by the in ter val be tween study time points and the level of fer til ity at the start.…”
Section: Fertility Preferences and Subsequent Childbearingmentioning
confidence: 99%